Analisis Tafsir Al-Qur’an tentang Relasi dan Manajemen Pendidikan Keluarga - Fawait Syaiful Rahman (Studia Quranika, 2022)
Interaction in the family becomes a major force in the cultivation of basic education for children. The family position is very strategic in terms of habituation of positive character for the child, especially the mother. The mother is the first madrasa or the education of the child. This means that children achieve a lot of learning from the mother figure, either as a figure who sets a positive example or as an educator who teaches direct knowledge. Family relations based on critical analysis of Qur'anic exegesis yield a conclusion: First, the family is the main environment forming positive or negative values. Both husbands' responsibilities are greater in the relationship of husband and wife or parents and children. The husband must be responsible for family education in order to give birth to a family building system that is sakinah, mawadah, warahmah. In addition, Family Education Management is the cooperation of family members on their respective duties and functions regarding education in the family. If the family consists of husband and wife called husband and wife relations then family education management is built by two husbands and wives to perform educational tasks and functions with a specific purpose. If the family part increases children, which is meant by the relationship of parents and children, then the implementation of family education management is the cooperation of parents to consistently carry out the duties and functions of education to children in the family, and so on.